2013
DOI: 10.1136/bcr-2013-200468
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma of the oesophagus: a rare cause of dysphagia

Abstract: Primary small cell carcinoma of the oesophagus is a rare, highly aggressive malignancy with diagnosis usually occurring at the most advanced stages. We report a case of small cell carcinoma of the oesophagus presenting with dysphagia and melena. A 79-year-old Caucasian man presented to an outside hospital with dizziness, light-headedness, chest pain and melena for 3 days. He had a history of intermittent dysphagia for solids and a 25-pound weight loss in the past 2 months. He underwent an esophagogastroduodeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…World Health Organization histological criteria (2004) for small cell lung cancer (SCLC) or SCEC include small, round, oval or spindle-shaped cells with scant cytoplasm, ill-defined cell borders, finely granular nuclear chromatin, and absent or inconspicuous nucleoli. IHC shows positive expression of the tumor markers CK8, AE1/AE3, EMA, Syn, NSE, CD56, Cg-A, and TTF-1[ 3 , 10 , 11 ]. Wang et al [ 10 ] showed that high Ki-67 expression was an independent favorable prognostic factor for PSCEC patients[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…World Health Organization histological criteria (2004) for small cell lung cancer (SCLC) or SCEC include small, round, oval or spindle-shaped cells with scant cytoplasm, ill-defined cell borders, finely granular nuclear chromatin, and absent or inconspicuous nucleoli. IHC shows positive expression of the tumor markers CK8, AE1/AE3, EMA, Syn, NSE, CD56, Cg-A, and TTF-1[ 3 , 10 , 11 ]. Wang et al [ 10 ] showed that high Ki-67 expression was an independent favorable prognostic factor for PSCEC patients[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with stage IIB/III disease who receive CT have a better MST than patients without CT (13.0 mo vs 6.1 mo), while those who receive CT combined with RT have a longer MST than patients who receive surgery combined with CT (25.7 mo vs 12.3 mo)[ 16 ]. CT can greatly improve the survival time of patients with stage III and IV disease[ 3 ]. The MST of patients with stage IV disease after CT is three times that of patients who don’t receive CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management consists of surgical esophagectomy in limited disease [ 8 , 9 ] and systemic chemotherapy in metastatic disease [ 10 ]. Few cases of PSSCE have been reported in the literature [ 11 13 ]. This report describes the case of a 36-year-old man presenting with epigastric pain, dysphagia, and melena due to a primary esophageal small cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%